ANALISIS PENGARUH AVERAGE DAY’S INVENTORY, AVERAGE COLLECTION PERIOD, AVERAGE PAYMENT PERIOD, DEBT TO EQUITY RATIO, CURENT RATIO, SIZE, DAN GROWTH TERHADAP PROFITABILITAS PERUSAHAAN - Fatiha, Cynthia Rahma; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2015)
The purpose of this study is to identify and analyze the factors that affect to return on assets (ROA) at manufacturing companies in 2010-2013. ROA is a dependent variable in this study, as an indicator of profitability. There are seven independent variables used, the average day's inventory, average collection period, average payment period, debt-to-equity ratio, current ratio, size, and growth. Sampling techniques is purposive sampling with certain criteria, ie companies listed on the Stock Exchange 2010-2013 period, so there are seventy-six datas as sample of one hundred fifty two manufacturing companies in Indonesia during the period 2010-2013. The data is processed by using a multiple linear regression equation with odinary least squares method using the SPSS program. The result showed that there is a negative and significant correlation between the average day’s inventory, average collection period, and debt to equity ratio to the ROA, while there is a positive and significant relationship between the Size to the ROA.